Significant Impact of Working Capital and Macroeconomic Condition on Profitability in Property Industry - Rizki, Achmad; Anggraeni, Lukytawati; Hardiyanto, Arief Tri (Jurnal Aplikasi Bisnis dan Manajemen, 2019)
Working capital management is important for managers to manage business operations smoothly and efficiently. This study investigates impact of working capital management and macroeconomic condition on profitability in Indonesian property industry. This study used data from the quarter financial report of 19 property firms listed in Indonesia Stock Exchange over the period 2011-2015 quarterly, while GDP, inflation, and interest rate data were obtained from Statistic Indonesia and Bank of Indonesia. The data were analyzed using panel data regression analysis. This study found that accelerating Cash Conversion Cycle (CCC) and being more aggressive in working capital policy would improve profitability. Furthermore, the result showed that macroeconomic condition, firm size, sales growth, and capital structure have significant effects on the profitability. Keywords: corporate finance, working capital, macroeconomic, profitability, property Abstrak: Manajemen modal kerja sangat penting bagi manajer dalam mengelola operasional bisnis agar berjalan secara lancar dan efisien. Studi ini meneliti dampak dari manajemen modal kerja dan kondisi makroekonomi terhadap profitabilitas di industri properti Indonesia. Penelitian ini menggunakan data dari laporan keungan secara kuartalan dari 19 perusahaan properti yang terdaftar di Bursa Efek Indonesia selama periode 2011–2015, sementara data PDB, inflasi, dan suku bunga didapatkan dari Badan Pusat Statistik dan Bank Indonesia. Data dianalisis menggunakan analisis regresi data panel. Penelitian ini menunjukan bahwa mempercepat siklus konversi kas dan lebih agresif dalam kebijakan modal kerja akan meningkatkan profitabilitas. Selanjutnya hasil penelitian menunjukkan bahwa kondisi ekonomi makro, ukuran perusahaan, pertumbuhan penjualan, dan struktur modal berpengaruh signifikan terhadap profitabilitas. Kata kunci: keuangan perusahaan, modal kerja, makroekonomi, profitabilitas, properti